2022
DOI: 10.1212/wnl.0000000000200150
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Multiple Sclerosis in the United States

Abstract: Background and Objectives:A recent report estimated that approximately one million adults were living with multiple sclerosis (MS) in the United States (US). While MS is rarely the direct cause of death, its debilitating effects on normal body functions can result in considerable disruption to daily living and life roles including work, physical independence, mobility, social interaction, and participation in leisure activities. This study estimated the total economic burden of MS in the US in 2019.Methods:Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 26 publications
1
56
0
Order By: Relevance
“…On a larger population level, the 2019 total estimated US economic burden of MS was $85 billion, and prescription medications (DMT and non-DMT) accounted for almost $40 billion of direct MS medical costs 117 . In recent years, costs of DMT have risen significantly, drastically out of proportion to the rate of inflation, and far outpace spending for clinical services 118 .…”
Section: Populations Of Special Interestmentioning
confidence: 99%
“…On a larger population level, the 2019 total estimated US economic burden of MS was $85 billion, and prescription medications (DMT and non-DMT) accounted for almost $40 billion of direct MS medical costs 117 . In recent years, costs of DMT have risen significantly, drastically out of proportion to the rate of inflation, and far outpace spending for clinical services 118 .…”
Section: Populations Of Special Interestmentioning
confidence: 99%
“…Consistent with published literature, the excess healthcare expenditures were defined as the additional healthcare expenditures that adults with osteoarthritis and pain incur compared to adults with osteoarthritis and no pain. 40 - 42 We performed analyses using SAS survey procedures (SAS v 9.4 (SAS Institute, INC)) and Stata 15 (StataCorp LLC, College Station, TX) for decomposition analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Additional barriers to accessing care include distance from health care providers (HCPs); costs of services, medication, and transportation; and inadequate health insurance coverage and reimbursement. [2][3][4] A 2007 study found that, in the United States, at least 31% of people with MS were unable to access the specialists their physician recommended they see. 5 We anticipate that with the advent of high-speed internet, inexpensive cameras, and monitoring software, telemedicine will continue to fill some of these gaps in care access for people with MS. 6,7 In early 2020, the COVID-19 pandemic produced multiple challenges for health systems throughout the world.…”
Section: Introductionmentioning
confidence: 99%